2001
DOI: 10.1016/s0378-5173(00)00685-2
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of natural anthocyanins by micellar Systems

Abstract: In this paper, we discuss the influence of different micellar systems on the degradation of natural anthocyans, either glycosides and aglycones, at pH values ranging from 2.8 to 6.0. The interaction of anthocyanins, in suitable dispersed systems such as negative micelles of sodium dodecylsulphate (SDS), consistently increased their chemical stability in aqueous solutions. The results of these experiments point out how both the number of available negative charges and the presence of an organised distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Another plausible molecular mechanism is associated with the reactivity of a chemical and its intermolecular interaction inside normal or reverse micelles. For example, it was reported elsewhere that anthocyanin derivatives were subject to an intermolecular selfassociation inside normal micelles (Mulinacci et al, 2001). This phenomenon was attributed to be responsible for increasing their chemical stability inside direct micelles.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Another plausible molecular mechanism is associated with the reactivity of a chemical and its intermolecular interaction inside normal or reverse micelles. For example, it was reported elsewhere that anthocyanin derivatives were subject to an intermolecular selfassociation inside normal micelles (Mulinacci et al, 2001). This phenomenon was attributed to be responsible for increasing their chemical stability inside direct micelles.…”
Section: Resultsmentioning
confidence: 95%
“…However, there have been few reports focusing on the chemical stability and reactivity of drugs with small molecular weights in reverse micelles (Mulinacci et al, 2001). Even though the effect of Tween surfactants upon TC solubility in water is reported elsewhere (Naggar et al, 1974), no reports have been made to scrutinize TC stability in a reverse micellar system.…”
Section: Introductionmentioning
confidence: 99%
“…The effect on stability was attributed to modified hydration and deprotonation of the Mal3glu molecule [25]. In another study using circular dichroism, anthocyanin stability was improved by association with anionic SDS micelles, with evidence of intermolecular self-association [26]. Improved stability of anthocyanins in lipophilic and amphipathic micellar environments has relevance to their behavior in vivo in bile and tissues.…”
Section: Anthocyanin Properties In Vivomentioning
confidence: 99%
“…The stabilising mechanism of SDS micelles towards natural colourants has been examined and discussed in relation to anthocyanins in literature; however, no exact mechanism has yet been conclusively made. Mulinacci et al, (2001) suggested that the presence of SDS micelles induced an intermolecular self-association process of the anthocyanins, which contributed to the increased stability. Liu, Fu, & Nian (2014) suggested that anionic surfactant micelles could isolate anthocyanins from variations in matrix acidity, while not affecting the characteristic colour of the anthocyanins due to the transparent nature of micelles.…”
Section: Mechanism Of Colour Stabilising Effect Of Sdsmentioning
confidence: 99%
“…Several reports have shown that anthocyanins can be stabilised by interaction with micelles formed from e.g. sodium dodecyl sulphate (SDS) (Mulinacci, et al, 2001;Lima, et al, 2002;Liu, Fu, & Nian, 2014). These reports conclude that the colour stabilisation occurs through interaction of the positively charged flavylium cation of anthocyanins with the negatively charged SDS micelle.…”
mentioning
confidence: 99%